Pengaruh Pendidikan Gizi dengan Media Booklet terhadap Pengetahuan Gizi Seimbang pada Remaja Putri di Pondok Pesantren Al-Hidayah Kota Jambi - Aulia Sari, Natasya; Yuli Fatmawati, Tina; Fati Hatussaadah, Siti (Poltekkes Kemenkes Bengkulu, 2025)
Adolescent girls are a vulnerable group to nutritional problems due to physiological changes and unhealthy eating habits. Low nutritional knowledge is a risk factor for poor nutritional status. Nutrition education using booklet media can be an effective strategy to improve balanced nutrition knowledge. This study aims to determine the effect of nutrition education using a booklet on balanced nutrition knowledge among adolescent girls at Al Hidayah Islamic Boarding School in Jambi City. This research employed a pre-experimental design with a one-group pretest-posttest approach. The sample was selected using proportional random sampling, involving 30 respondents. Data were collected using a balanced nutrition knowledge questionnaire administered before and after the distribution of the booklet. Data analysis was conducted using the Paired Sample T-Test. The results showed an increase in the average knowledge score from 25.18 ± 12.18 to 78.89 ± 15.94, with a p-value of 0.000 (p < 0.05), indicating a statistically significant difference. Conclusion: Booklet media is effective in increasing balanced nutrition knowledge among adolescent girls in Islamic boarding schools.